Vertical aerosol profiles and the impact of regional transport in a background region of Northwest China: Insights from ground-based lidar - Kai Cheng; Xia Li; Yaqiong Kuang; Yuting Zhong; Haiyang Cai; Shuting Li (Atmospheric Research, 2026)

Lignin-polyphenol epoxy layer: a multi-functional protective coating cascade-constructed by ionic liquids - Cheng Li; Yuting Shi; Wenzhe Xiao; Xiaoning Wang; Wanting Zhao; Wenjin Li; Shangru Zhai; Jian Sun (Bioresource Technology, 2026)

Decadal gelatinization and phenological advancement of small jellyfish in Laizhou Bay, Bohai Sea - Ping Fu; Shan Sun; Huichao Jiang; Jianlong He; Ling Cheng; Bo Su; Hongyan Xing; Yuanqing Ma; Lijuan Liu; Yuting Zhao; Juan Zhang; Xiaowen Zhang (Marine Pollution Bulletin, 2026)

Structural and functional characterization of whey protein isolate-polyphenol covalent conjugates prepared via electrochemical oxidation, alkaline treatment, and free radical grafting - Jinshun Ye; Ying Xu; Yuting Li; Wenxue Cheng; Xiaozhen Liu; Xiangying Yu; Jingkun Yan; Lin Li (Food Research International, 2026)

Self-adhesive small intestinal submucosa-based hydrogel patch with dual-stage sequential curcumin release for pulmonary air leak sealing, sustained anti-inflammatory modulation, and lung regeneration - Yuting Cheng; Daping Yu; Zixun Wang; Bo Zhao; Pengfei Wei; Wei Jing; Yiqian Huang; Yuxin Guo; Huimin Li; Xuening Wang; Peng Jiao; Yandong Li; et al. (Chemical Engineering Journal, 2026)

Impacts of freeze-thaw cycles on soil aggregate stability and phosphorus occurrence under different land uses - Yuting Cheng; Shuhao Hao; Jiaxin Zhang; Guoce Xu; Yi Zhang; Zongping Ren; Wenting Jiang; Maolin Liu (Soil and Tillage Research, 2026)

From protein structural reconfiguration to long-term emulsion stabilization: How ultrasound-microwave synergistic modulates no-added-salt myofibrillar protein-based emulsions through multiscale interfacial assembly - Yufeng Chen; Siqi Lan; Jipeng Gu; Weiwei Cheng; Xuxia Zhou; Shulai Liu; Yuting Ding (Food Chemistry, 2026)

Zearalenone-induced hepatotoxicity: Underlying mechanisms and genistein-mediated preventive effects - Ruo Du; Qingyuan Li; Yi Cheng; Yuting Zeng; Mairewulan Abula; Wenyi Liu; Fangfang Yu; Weihua Jia; Yuhui Du; Yue Ba; Yanjie Wang; Guoyu Zhou (Food and Chemical Toxicology, 2026)

TCSwinPNet: a lightweight tri-branch convolutional Swin Transformer network with hybrid feature injection for Multispectral and panchromatic image fusion - Zechun Li; Xunqiang Gong; Xiong Xu; Yichuang Luo; Yuting Wan; Ailong Ma; Haiqin Cheng; Rong Liu; Yanfei Zhong (International Journal of Remote Sensing, 2026)

Post-scour reliability assessment of offshore monopiles incorporating field monitoring data and multivariate Gaussian modelling - Yuting Zhang; Kai Wen; Qiang Li; Xinglei Cheng; Haoran Ouyang; Jiawei Xie; Yanhao Zheng (Ocean Engineering, 2026)

Integrated transcriptomic and metabolomic analyses reveal the differential response mechanisms of Gymnocypris eckloni gills to different intensities of acute heat stress - Wenzhuo Ban; Rongrong Liao; Yuting Duan; Mei Peng; Cheng Chen; RenYi Yang; Yinhua Zhou; ZhaoFang Han; Haiping Liu; Luo Lei; Chaowei Zhou (Journal of Thermal Biology, 2026)

Molecular orchestration of highland barley starch-β-glucan complexes under extrusion thermomechanics: linking hierarchical structure to digestive resistance - Liping Fu; Yingting Zhao; Xinyi Chen; Lujie Cheng; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Research International, 2026)

Mechanism of pH-driven gelation in Tremella fuciformis polysaccharide-soy protein isolate composite systems - Yingting Zhao; Danni Wang; Xinyi Chen; Lujie Cheng; Liangfeng Ma; Qisen Xiang; Yuting Tian (Food Chemistry, 2026)

Thermodynamics-electronics synergism in defect passivation enables highly efficient and stable lead-free copper-based halide perovskites - Yongfeng Lu; Yuting Tong; Fangyi Zha; Zhenyu Hu; Liping Gui; Hongrui Cheng; Yuhang Liang; Yuanhui Zheng (Chemical Engineering Journal, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Enzyme-hydrolyzed polysaccharides from Morchella importuna: preparation, structural characterization, and multi-omics of lipid metabolism regulation - Dongjie Li; Heng Miao; Ruru Liu; Xu Pan; Yuting Pei; Guoqing Wei; Xueran Geng; Yanfen Cheng; Junlong Meng; Ludan Hou; Mingchang Chang; Lijing Xu (Food Chemistry, 2026)

Partial debranching and microwave treatment stabilize amylopectin-flavor interactions for better tsampa processing outcomes - Xinyi Chen; Liping Fu; Ye Xu; Lujie Cheng; Zijian Huang; Wenhui Zhang; Qisen Xiang; Yang Liu; Yuting Tian; Yingting Zhao (Carbohydrate Polymers, 2026)

Systemic Control Failures on Offshore Installations: A STAMP-Based Analysis of the Penglai 19-3 Accidents and Comparison with Deepwater Horizon - Xingwei Zhen; Jan-Erik Vinnem; Yuting Cheng (Journal of Marine Science and Engineering, 2026)
The 2011 Penglai (PL) 19-3 oil spills in China’s Bohai Sea, resulting from two subsea accidents within a month and contaminating 6200 km2, represent the nation’s worst offshore pollution disaster. Yet, systemic analysis of lessons learned remains notably limited. The April 2021 blowout and fire at the same field, resulting in three fatalities, highlights the continuing relevance of the PL 19-3 case and the need to re-examine the 2011 accidents in depth. This study therefore focuses on the 2011 case as a systematically investigated instance to identify control failures that may explain recurring major risks at the field. This study develops a Systems-Theoretic Accident Model and Processes (STAMP)-based approach to systematically deconstruct the PL 19-3 accidents and benchmark their root causes against those of the 2010 Deepwater Horizon (DWH) disaster. Blowouts and well control incidents in the Norwegian sector are also mentioned to illustrate the well control hazard. The analysis identifies systemic control failures at the regulatory, organizational, and operational levels, revealing that the majority of human and organizational root causes identified are common to both accidents. Based on these findings, an integrated reform framework is proposed, comprising co-regulation models adapted from Norwegian practices, a national major hazard risk indicator system, and mandatory barrier management. This study contributes a theoretically grounded accident analysis and provides empirically informed policy recommendations for controlling major hazard risks in offshore petroleum activities.

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Survival-enhancement potential of tea polyphenol-chitosan composites for Pacific oysters (Crassostrea gigas) during anhydrous low-temperature preservation and its multiple mechanisms - Weiwei Cheng; Chen Chen; Jiangxiang Wang; Sohail Khan; Yufeng Chen; Zhigang Ke; Xuxia Zhou; Yuting Ding; Shulai Liu (Food Chemistry, 2026)

Disulfidptosis in hepatocellular carcinoma: molecular mechanisms, therapeutic potential, and exploratory insights into chronic liver diseases - Yuting Liu; Wenzhuo Hu; Jingyin Mai; Yang Cheng (Apoptosis, 2026)

Solvent design principles for porous liquids and prospects for CO₂ capture applications - Yixin Zheng; Jiacan Zhu; Yuting Li; Jiaying Miao; Wenxuan Huang; Qingyi Gou; Xingyong Li; Di Cai; Qingsong Cheng; Jianbo Zhao (Journal of Water Process Engineering, 2026)

Decoding volatile compound-aroma attribute correlations in representative Oolong Teas of Fujian: An integrated objective quantification and GC–MS profiling method - Chengzhe Zhou; Jiaxin Fang; Shuaibo Shao; Cheng Zhang; Caiyun Tian; Zhengdong Zhang; Anru Zheng; Yuting Li; Siwei Deng; Changlian Wu; Shengjing Wen; Nadang Long; et al. (Food Chemistry, 2026)

Pectin from Phyllanthus emblica L.: Structure elucidation and synergistic in vitro anti-stomach adenocarcinoma effects with 5-fluorouracil - Haotian Huang; Jiajie Chen; Ran Cheng; Yihan Wang; Yuting Zeng; Yanzhen Wang; Dongsheng Yang (Carbohydrate Polymers, 2026)

Understanding of a sudden shift from foehn to late spring cold span on the north slope of the Middle Tianshan Mountains with meteorological observation and terrain sensitivity simulation experiments - Maoling Ayitikan; Alaiyi Aiding; Yusufu Musha; Qing He; Chengguang Yang; Wulifan Hanan; Shuting Li; Yuting Zhong; Kai Cheng (Journal of Mountain Science, 2026)

Smart funoran film incorporated with blueberry anthocyanins as a dual pH/NH3 sensor for real-time monitoring of shrimp freshness - Sohail Khan; Zhongming Bao; Abdullah; Jiangxiang Wang; Xuxia Zhou; Yuting Ding; Weiwei Cheng; Shulai Liu (Food Hydrocolloids, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

Quantitative western blotting adapted for expanded sample capacity with non-linear curve fitting - Yuting Cheng; Junko Kishimoto; Zihao Ye; Ayu Narita; Xueyun Hu; Hisashi Ito; Ryouichi Tanaka (Journal of Plant Research, 2026)

Study on the mechanism of flavor development in ultrasound-assisted microwave vacuum drying of shiitake mushrooms: Dosage effect of ultrasonic amplitude - Lujie Cheng; Hanbing Xiao; Dongkun Tu; Yingting Zhao; Yong Lin; Qisen Xiang; Yuting Tian (Food Chemistry, 2026)

PpERF.E3 regulates peach fruit ripening and softening by mediating ethylene biosynthesis and cell wall degradation - Xingzhen Zhang; Tongyang Kang; Lijun Cao; Qianjin Zhan; Yuting Xu; Jingwen Zhu; Xuyang Zheng; Xi Cheng; Yanan Hu; Caiping Zhao (Postharvest Biology and Technology, 2026)

A deep learning-based two-stage feature matching method for small celestial body 3D shape reconstruction - Falin Wu; Jingyao Yang; Guoxin Qu; Yushuang Liu; Haoxin Li; Yuting Cheng; Dongjing Yang (Icarus, 2026)

Sustainable recovery of phospholipid-enriched polar lipids from scallop processing wastes for multifunctional application - Weiwei Cheng; Jiangxiang Wang; Xinyang Li; Lukai Ma; Sohail Khan; Yufeng Chen; Zhigang Ke; Xuxia Zhou; Yuting Ding; Shulai Liu (Food Chemistry, 2026)

The impact of storage conditions on quality and shelf life of fresh-cut jackfruit: a metabolomics perspective - Yuting Huang; Wenli Zhang; Wanqing Sun; Wenzhu Shen; Yifan Cheng; Yining Xia; Yanjun Zhang; Qiong Lin (Food Chemistry, 2026)

Electrosynthesis of H2O2 through water oxidation reaction: Mechanisms, catalysts, and prospects - Xiahui Huang; Yuting Li; Jie Cheng; Yinghuan Xu; Jiacan Zhu; Ruilan Liu; Yongyan Xu; Jianbo Zhao; Kaipeng Cheng; Zhenjiang Cao (Chemical Engineering Journal, 2026)

Chemical composition, source apportionment and formation mechanisms of PM2.5 in urban and background areas of northwestern China - Kai Cheng; Yuting Zhong; Xinchun Liu; Xia Li; Maulen Ayitken; Shuting Li; Hongna Chen; Bingbing Leng; Wang Zhang; Haiyang Cai (Atmospheric Pollution Research, 2026)

Mitochondrial Gene Signature Reveals Novel Diagnostic Biomarkers for Autism Spectrum Disorder - Jieyu Wang; Zeyu Cheng; Mingyuan Liu; Yuting Zhang; Yi Jiang; Tianyu Liu; Junyu Ren; Lijie Wu; Mingyang Zou; Caihong Sun (Molecular Neurobiology, 2026)

Thinning altered the response of GPP to environmental factors in a coniferous plantation in Southern China - Shengtong Li; Mingjie Xu; Fengting Yang; Yuting Wang; Jiaxin Song; Baoxin Shan; Ziyi Wang; Huimin Wang; Xianjin Zhu; Chuanpeng Cheng; Jianlei Wang; Tao Zhang (International Journal of Biometeorology, 2026)

A dual crosslinking strategy to enhance the quality stability of surimi gels at 115 °C under high-pressure: An underlying mechanism - Yufeng Chen; Fangdong Yang; Weiwei Cheng; Qingyu Hong; Hongyun Yan; Xuxia Zhou; Yuting Ding; Shulai Liu (Food Research International, 2025)

Effects of different sour off-flavor in jumbo squid (Dosidicus gigas) on brain perceptions via scalp electroencephalogram and the underlying mechanisms - Jiangxiang Wang; Zhigang Ke; Weiwei Cheng; Xingran Kou; Xuxia Zhou; Yuting Ding; Shulai Liu (Food Research International, 2025)

Enhancing fruity aroma of Cabernet Sauvignon wine by mixed culture fermentation with Schizosaccharomyces japonicus, Saccharomyces cerevisiae, and Starmerella bacillaris - Yuting Chen; Chunxiao Wang; Zhanyan Zhang; Cheng Wu; Angxin Song; Yuangen Wu (Food Microbiology, 2025)

Synergistic valorization of red mud and spent coffee grounds via one-step hydrothermal carbonization for high-efficiency Pb(II) and Cd(II) removal from wastewater - Yuting Cui; Yue Zhou; Mingqian Cheng; Wei Fang; Yaoling Wang; Chao Chen; Tingting Liu; Bin Li; Zewei Liu (Desalination, 2025)

The Holocene stalagmite trace element and Sr isotope records from Central China and the inferred hydroclimate changes - Yuting Wu; Yanjun Cai; Fugui Xiao; Mei He; Shouyi Huang; Xiangkun Zhai; Ruoxin Li; Gang Xue; Hanying Li; Chunlei Zong; Hai Cheng (Chemical Geology, 2025)

The whole genome sequence of Cordyceps cicadae — an edible and potential medicinal fungus - Yuwei Liu; Xueqian Li; Yiqi Meng; Yifan Wu; Yuting Jin; Xiaotong Ma; Wei Zhou; Yuchong Tan; Fu-Cheng Lin; Hongkai Wang (Molecular Genetics and Genomics, 2025)

Using urban-suburban difference of atmospheric CO2 to evaluate carbon neutrality capacity in Hangzhou, China - Bing Qi; Cheng Hu; Yan Yu; Yuting Pang; Fangqi Wu; Xinjie Yang; Huili Liu; Junqing Zhang; Qitao Xiao; Cheng Liu; Wei Xiao (Journal of Environmental Sciences, 2025)

Determining the differences in O3-NOx-VOCs sensitivity between sauna and roast days - Yuting Liu; Yinghong Wang; Yusi Liu; Mengtian Cheng; Baoxian Liu; Tao Song; Bo Hu; Dan Yao; Miao Yu; Yu Shi; Guiqian Tang; Yuesi Wang (Journal of Environmental Sciences, 2025)

Numerical simulation of droplet formation for non-Newtonian power-law fluids in flow-focusing microchannels by lattice Boltzmann method - Shiteng Wang; Hao Wang; Yuting Wu; Yi Cheng (Chemical Engineering Journal, 2025)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Low-temperature De-NOX of M-MnFe2O4 derived from MOFs: Experiments and DFT calculations - Yuting Hu; Minghu Zhao; Kai Qin; Ting Cheng; Taotao Liu; Chengzhu Zhu (Process Safety and Environmental Protection, 2025)

Exogenous melatonin activates BoNAC52-BoRBOHF module and antioxidant system involved in the delay in broccoli yellowing during postharvest - Yue Wang; Lufan Wang; Yuting Li; Wenbo Lei; Jianhui Cheng; Yuan Cheng; Shuling Shen; Lanying Yao; Lichao Zhou; Yan Liu; Xiaolin Zheng; Chen Huan (Postharvest Biology and Technology, 2025)

Organic materials input promotes the soil aggregate sequestration through changing soil aggregates structure and stability - Wenting Jiang; Tingting Li; Jifu Ma; Xiukang Wang; Yuting Cheng; Lei Gong; Jie Zhang; Guoliang Chen (Journal of Environmental Management, 2025)

Spatiotemporal variation and drivers of ecosystem service value: A case study in Ziwuling area, Loess plateau - Fengyou Gu; Guoce Xu; Bin Wang; Yuting Cheng; Mingzhu Xu; Jing Li (Journal of Environmental Management, 2025)

Effects of airborne ultrasonic coupled microwave vacuum drying on moisture-heat migration and quality characteristics of shiitake mushrooms - Dongkun Tu; Lujie Cheng; Ye Xu; Yuxin Cheng; Yuhua Huang; Yingting Zhao; Qisen Xiang; Yuting Tian (Food Research International, 2025)

Effect of the roasting process on the flavor formation of Tibetan pork: Matrices oxidation dependence on temperature or time - Qia Wang; Lujie Cheng; Yingmei Wu; Yingqun Wu; Qisen Xiang; Xiefei Li; Fengping An; Hongbo Song; Xin Li; Yuting Tian; Qun Huang (Food Chemistry, 2025)

A Study on the Impact of α-Fe2O3 NPs, Biochar, and Their Composite Treatments on the Gene Expression Response of Muskmelon under Cadmium Pollution - Junli Li; Shouyue Wang; Zhenkai Liu; Yuxuan Cheng; Haotian Li; Riping Duan; Yuting Shi; Yunqiang Wang (Water, Air, & Soil Pollution, 2025)

Nitrogen addition affects the phosphorus fraction of rhizosphere soil in young forest plantations - Fengna Liang; Chaobin Xu; Josep Peñuelas; Jordi Sardans; Yuting Li; Yunni Chang; Dongliang Cheng; Shushu Yao; Quanlin Zhong (Plant and Soil, 2025)

Enhanced lignocellulose degradation and humification during the co-composting of cattle manure and tree branches: Synergism of microbial inoculation, biochar, and MnO2 - Wengao Shangguan; Muyuan Zhang; Shang Cheng; Dan Song; Yiyuan Wei; Mengjuan Wang; Xiaoxuan Su; Yuting Zhang; Ran Xiao (Process Safety and Environmental Protection, 2025)

Simultaneous determination of 202 pesticide residues and 19 mycotoxins in coix seed by QuEChERS coupled with LC-Q-TOF/MS and subsequent assessment of dietary exposure risk - Rui Cheng; Yujie Xie; Qiaoying Chang; Yuting Bai; Kaixuan Tong; Xingqiang Wu; Hui Chen (Food Control, 2025)

Tailored platelet biomimetic delivery platform for targeted therapy of inflammatory bowel disease - Yue Li; Yayue Zhang; Xuran Ding; Taotao Zou; Hu Li; Ke Xu; Cheng Su; Yuting Wang; Ziming Zhao; Yuan He (Chemical Engineering Journal, 2025)

Corrigendum to “Facilitating lignocellulose fractionation of Moringa oleifera Lam. husk by pretreatment with a novel 1-tetradecyl-3-carboxymethylimidazolium bromide-based deep eutectic solvent” Journal of Cleaner Production 483 (2024) 144249 - Jiabo Cheng; Yuan Gao; Jie Liu; Yuting Zhang; Mengfei Tian; Mengying Zhang; Yaru Zhang; Chunjian Zhao; Chunying Li (Journal of Cleaner Production, 2025)

Enzymatic characteristics and catalytic mechanisms of opine dehydrogenases from jumbo squid (Dosidicus gigas) for acidic opine formation - Weiwei Cheng; Jiangxiang Wang; Jiahe Xu; Sohail Khan; Hongyun Yan; Yufeng Chen; Zhigang Ke; Xuxia Zhou; Yuting Ding; Shulai Liu (Food Research International, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Electrocatalytic membrane-driven ozonation to reconstruct the extracellular polymeric substance for enhanced sludge dewatering - Yantao Song; Wei Zhang; Zhenao Gu; Yu Cheng; Haihua Bao; Jiaqi Wang; Ning Wang; Yuting Liu; Zongqiang Zhu; Chengzhi Hu (Journal of Water Process Engineering, 2025)

Preparation of integrated catalytic filter bag by Eu/MnTiOx for de-NO of industrial kiln flue gas - Yuting Hu; Zhaozhong Jiang; Kang Cheng; Qiaoqin Xie; Chengzhu Zhu; Taotao Liu (Journal of Environmental Chemical Engineering, 2025)

Preparation, characterization and potential mechanisms of 3D-printed meat analogs based on soy protein isolate-wheat gluten protein by L-cysteine cross-linking - Zhi Cheng; Yue Qiu; Xinglan He; Ruizhi Yang; Liyan Zhao; Gaopeng Zhang; Jianyou Zhang; Yuting Ding; Fei Lyu (Food Research International, 2025)

Attention-guided multi-task network for streak-like dim and small space target detection in single optical images - Falin Wu; Haoxin Li; Guoxin Qu; Chunxiao Zhang; Yushuang Liu; Jingyao Yang; Dongjing Yang; Yuting Cheng (Advances in Space Research, 2025)

Migrasome-related ITGA5 for predicting prognosis, immune infiltration and drug sensitivity of hepatocellular carcinoma - Wanjin Chen; Kailin Liu; Zhiling Wang; Hui Zhang; Ming Tan; Yuting Liu; Tingting Gao; Xiameng Su; Leirong Gu; Xinyan Chen; Shengtao Cheng (Apoptosis, 2025)

Psychedelics for treating psychiatric disorders: from circuit mechanisms to applications - Jie Li; Yuting Jiang; Dan Cheng; Jianjun Cheng; Ji Hu; Xiaohui Wang; Ti-Fei Yuan (Science Bulletin, 2025)

Advancing spatial-temporal rock fracture prediction with virtual camera-based data augmentation - Jiawei Xie; Baolin Chen; Jinsong Huang; Yuting Zhang; Cheng Zeng (Tunnelling and Underground Space Technology, 2025)

Odor-induced saltiness enhancement of volatile compounds screened from duck stewed with chili pepper - Yue Qiu; Xinglan He; Wenbo Zheng; Zhi Cheng; Jianyou Zhang; Yuting Ding; Fei Lyu (Food Chemistry, 2025)

Effect of the ocean tide on the Earth nutation: An updated assessment - Yuting Cheng; Christian Bizouard (Advances in Space Research, 2025)

Changes in water conservation and a new estimation for its future potential - Mingzhu Xu; Guoce Xu; Shibo Liu; Jing Li; Zhanbin Li; Yuting Cheng; Jie Zhuang; Yutong Dang; Bin Wang; Fengyou Gu (CATENA, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

Enhancement of structural properties of 3D-printed plant-based meat analogs by TGase/laccase - Zhi Cheng; Yue Qiu; Ishtiaq Ahmad; Yuting Pang; Aodong Yue; Zhangxi Chen; Gaopeng Zhang; Yuting Ding; Fei Lyu (Journal of Food Engineering, 2025)

Enhancing walnut butter with a pea protein isolate-pectin-pterostilbene complex: Physicochemical properties and stability analysis - Zonghui Tang; Panchen Fang; Yuting Tao; Qiuye Huang; Xuefei Xu; Xiaoyan Cheng; Faraz Hussain; Xueling Li; Jin Liang; Shuming Ye; Yue Sun (Food Research International, 2025)

Ultrasound-assisted microwave vacuum drying enhances flavor release during stewing of dried shiitake mushrooms - Dongkun Tu; Ye Xu; Yuxin Cheng; Yuhua Huang; Yingting Zhao; Yuting Tian (Food Chemistry, 2025)

Assessment of pollution sources and health risks of black carbon aerosols in industrial cities of Northwestern China using light absorption observations - Kai Cheng; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken; Wang Zhang; Xinchun Liu (Atmospheric Pollution Research, 2025)

Isolation, purification, characterization and stability analysis of melanin pigment from Mesona chinensis - Yuhua Huang; Hongzhang Zhu; Yuxin Cheng; Can Zhao; Ye Xu; Zhiao Wang; Xinliang Chen; Yingting Zhao; Yuting Tian (Food Chemistry, 2025)

Remediation of Cd-As-Ni co-contaminated soil by extracellular polymeric substances from Bacillus subtilis: Dynamic improvements of soil properties and ecotoxicity - Yang Li; Lei Cheng; Baolin Yang; Yanan Zhao; Yuting Ding; Chenxi Zhou; Yuanyuan Wu; Ruoyun Dong; Yun Liu; An Xu (Science of The Total Environment, 2024)

Printing characteristics and microwave infrared-induced 4D printing of chestnut powder composite paste - Yinqiao Lv; Bo Wang; Yuting Cheng; Weiqiao Lv; Shiyu Zeng; Hongwei Xiao (Journal of Food Engineering, 2024)

Facilitating lignocellulose fractionation of Moringa oleifera Lam. husk by pretreatment with a novel 1-tetradecyl-3-carboxymethylimidazolium bromide-based deep eutectic solvent - Jiabo Cheng; Yuan Gao; Jie Liu; Yuting Zhang; Mengfei Tian; Mengying Zhang; Yaru Zhang; Chunjian Zhao; Chunying Li (Journal of Cleaner Production, 2024)

Boosting H2O2 activation by Cu and Ce co-doped g-C3N4 for pollutants removal: From the free radical pathway to the non-free radical pathway - Qinghua Zou; Qingkai Shi; Min Cheng; Guangfu Wang; Wenjun Wang; Yongxi Chen; Ao Chen; Yuting Ma (Journal of Environmental Chemical Engineering, 2024)

Polyphenol compounds contributing to the improved bioactivities of fermented Rubus chingii Hu - Yuhan Cheng; Yuting Wang; Tongji Yuan; Jianhua Xie; Qiang Yu; Yi Chen (Food Research International, 2024)

Corrigendum to ‘A facile synthesis of Ag3PO4/BiPO4 p-n heterostructured composite as a highly efficient photocatalyst for fluoroquinolones degradation’ [Environ. Res. 203 (2022) 111843] - Xin Zhu; Yu Yan; Yuting Wang; Tao Long; Jinzhong Wan; Cheng Sun; Yang Guo (Environmental Research, 2024)

Blocking endogenous phosphorus release in sediments by a hydrotalcite mixture synthesized with natural sepiolite and discarded cans - Fulong Cheng; Jie Pan; Changxin Zhao; Wei Li; Yuting Peng; Zuo Zhang; Yanjuan Lin; Guowen Chen (Applied Clay Science, 2024)

Simulation study on heavy metals, phthalate esters, and organic halogens: Content and distribution characteristics during waste paper recycling - Lingyun Cheng; Bo Yue; Bangbang Meng; Tao Wang; Yuting Liang (Environmental Science and Pollution Research, 2024)

Effective adsorption performance and mechanism of methylene blue from dye wastewater by humic acid sucrose-modified red mud - Wei Fang; Yue Zhou; Mingqian Cheng; Jinzhong Yang; Qifei Huang; Zechun Huang; Yuting Cui; Liping Zhang; Yushu Wang; Qihong Cen; Zewei Liu; Bin Li (Process Safety and Environmental Protection, 2024)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

Dose-dependent effects of different parabens on food waste biorefinery for volatile fatty acids production: Insight into specific fermentation processes, substrates transformation and microbial metabolic traits - Ziyu Li; Yuting Dou; Zhenzhou Li; Yujie Yuan; Qin Zhang; Song Cheng; Xiaoshi Cheng; Jingyang Luo (Science of The Total Environment, 2024)

Exogenous melatonin delays yellowing in postharvest broccoli by regulation of ABA and carotenoid metabolite - Ran Yan; Mariama Kebbeh; Yuan Cheng; Yue Wang; Yuting Li; Maorun Fu; Yan Liu; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2024)

Light-powered biodegradation of Imidacloprid by Scenedesmus sp. TXH202001: Assessing complete removal, metabolic pathways, and toxicity verification - Yongtao Cheng; Hongyu Wang; Yuanyuan Wu; Yuting Ding; Chuanyue Peng; Cuicui Qi; An Xu; Ying Liu (Journal of Hazardous Materials, 2024)

Interception of internal phosphorus release from sediments by lanthanum-modified shrimp shell biochar in two application modes - Fulong Cheng; Zuo Zhang; Changxin Zhao; Yuting Peng; Maoyu Liao; Jianxin Fan (Journal of Cleaner Production, 2024)

Continuous flow hydrothermal synthesis of MoVNbTeOx in micro-coil tubular reactor for oxidative dehydrogenation of ethane - Yuxin Chen; Yuting Wu; Shuairen Qian; Zhengwen Li; Changyan Xu; Ruiqi Du; Yao Mu; Tianying Dai; Binhang Yan; Yi Cheng (Chemical Engineering Journal, 2024)

Zinc oxide/graphene oxide nanocomposites specifically remediated Cd-contaminated soil via reduction of bioavailability and ecotoxicity of Cd - Yang Li; Lei Cheng; Baolin Yang; Yuting Ding; Yanan Zhao; Yuanyuan Wu; Yaguang Nie; Yun Liu; An Xu (Science of The Total Environment, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Centrifuge shaking table tests on tiered reinforced soil retaining walls subjected to the excitations of near-field ground motions - Cheng Fan; Xuejun Liu; Yuting Zhang; Xiaoyu An; Huabei Liu (Geotextiles and Geomembranes, 2024)

Highly uniform organic nanowire synaptic arrays with excellent performance for associative memory - Hongyi Hong; Zunxian Yang; Yuliang Ye; Songwei Ye; Zhiming Cheng; Zhiwei Zeng; Zongyi Meng; Qianting Lan; Hui Zhang; Ye Chen; Jiaxiang Wang; Yuting Bai; et al. (Chemical Engineering Journal, 2024)

Arenobufagin regulates the p62-Keap1-Nrf2 pathway to induce autophagy-dependent ferroptosis in HepG2 cells - YuTing Yang; Chun Liu; Meng Wang; Hui Cheng; Huan Wu; ShengYong Luo; Mei Zhang; XianChun Duan; Qinglin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Carbon pools in forest systems and new estimation based on an investigation of carbon sequestration - Bin Wang; Guoce Xu; Zhanbin Li; Yuting Cheng; Fengyou Gu; Mingzhu Xu; Yixin Zhang (Journal of Environmental Management, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Muscle fibrous structural design of plant-based meat analogs: Advances and challenges in 3D printing technology - Zhi Cheng; Yue Qiu; Mengyao Bian; Ying He; Shengke Xu; Yan Li; Ishtiaq Ahmad; Yuting Ding; Fei Lyu (Trends in Food Science & Technology, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Effect of xanthan gum on physicochemical properties and 3D printability of emulsion-filled starch gels - Yuting Cheng; Bo Wang; Weiqiao Lv; Yuanliang Zhong; Guohua Li (Food Hydrocolloids, 2024)

Enhancing the bioavailability of quercetin via the construction of carboxymethylated curdlan/quercetin nanocomplex - Yuting Su; Qian Zhou; Hui Xu; Manting Huang; Siqian Li; Jiayi He; Ka-Wing Cheng; Mingfu Wang (Food Hydrocolloids, 2024)

Source apportionment and health risk assessment of PM2.5-bound elements on winter pollution days in industrial cities on the northern slope of Tianshan Mountain, China - Kai Cheng; Youjiang He; Yuting Zhong; Xia Li; Shuting Li; Maulen Ayitken (Atmospheric Pollution Research, 2024)

Establishment of a hydrodynamic delivery system in ducks - Zhanji Zhao; Jiabing Zhu; Lijian Zhou; Nan Sun; Kaile Chang; Xiaoyue Hu; Yuting Hu; Mingzhi Ren; Yan Cheng; Derong Xu; Hongbo Xin; Chunbo Zhang (Transgenic Research, 2024)

Overexpression of Nrf2 reverses ferroptosis induced by Arenobufagin in gastric cancer - Jiao Long; Wenjun Wang; Jing Chu; Yueyue Li; Meng Wang; Jingjing Su; Yuting Yang; GuoKai Wang; Qinglin Li; Hui Cheng (Toxicology and Applied Pharmacology, 2024)

Alterations in sperm DNA methylation may as a mediator of paternal air pollution exposure and offspring birth outcomes: Insight from a birth cohort study - Yuting Cheng; Jialin Feng; Jing Wang; Yijie Zhou; Shengjun Bai; Qiuqin Tang; Jinhui Li; Feng Pan; Qiaoqiao Xu; Chuncheng Lu; Wei Wu; Yankai Xia (Environmental Research, 2024)

Whether rural rooftop photovoltaics can effectively fight the power consumption conflicts at the regional scale – A case study of Jiangsu Province - Yuting Yang; Zhiyuan Si; Ling Jia; Peng Wang; Lei Huang; Yanan Zhang; Cheng Ji (Energy and Buildings, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

A multifunctional interface optimization strategy for efficient Quasi-2D blue perovskite Light-Emitting diodes - Yuliang Ye; Zhou Cui; Zunxian Yang; Zhiwei Zeng; Zongyi Meng; Hongyi Hong; Songwei Ye; Zhiming Cheng; Qianting Lan; Jiaxiang Wang; Ye Chen; Hui Zhang; et al. (Chemical Engineering Journal, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Spatiotemporal differences in tropospheric ozone sensitivity and the impact of “dual carbon” goal - Yuting Liu; Guiqian Tang; Yinghong Wang; Mengtian Cheng; Jian Gao; Yuesi Wang (Science Bulletin, 2024)

Study of molecular interaction and texture characteristics of hydrocolloid-mixed alginate microspheres: As a shell to encapsulate multiphase oil cores - Yuting Wu; Boya Lv; Shiteng Wang; Zhe Liu; Xiao Dong Chen; Yi Cheng (Carbohydrate Polymers, 2024)

The impact of resource-based city construction on the green intensive use of resources - Ziwan Zeng; Zhonghua Cheng; Yuting Hang (Environment, Development and Sustainability, 2024)

Exposure to particulate matter may affect semen quality via trace metals: Evidence from a retrospective cohort study on fertile males - Yuting Cheng; Jiaqi Zhu; Qiuqin Tang; Jing Wang; Jialin Feng; Yijie Zhou; Jinhui Li; Feng Pan; Xiumei Han; Chuncheng Lu; Xinru Wang; Marvin E. Langston; et al. (Chemosphere, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Paris polyphylla saponins II inhibits invasive, migration and epithelial-mesenchymal transition of melanoma cells through activation of autophagy - Hui Cheng; Jing Chu; Yuting Yang; Yueyue Li; Meng Wang; Huan Wu; Manman Wang; Jingjing Su; Qinglin Li (Toxicon, 2024)

Egg yolk powder-starch gel as novel ink for food 3D printing: Rheological properties, microstructure and application - Yuanliang Zhong; Bo Wang; Weiqiao Lv; Guohua Li; Yinqiao Lv; Yuting Cheng (Innovative Food Science & Emerging Technologies, 2024)

Vertical distribution of VOCs in the boundary layer of the Lhasa valley and its impact on ozone pollution - Dan Yao; Yinghong Wang; Zhixuan Bai; Mengtian Cheng; Guiqian Tang; Yuting Liu; Deqing Zhuoga; Hao Yu; Jianchun Bian; Yuesi Wang (Environmental Pollution, 2024)

Combination of biochar and PGPBs amendment suppresses soil-borne pathogens by modifying plant-associated microbiome - Wenkang Yan; Yuting Liu; Antonino Malacrinò; Jiaoyang Zhang; Xiaoli Cheng; Christopher Rensing; Zhongyi Zhang; Wenxiong Lin; Zhen Zhang; Hongmiao Wu (Applied Soil Ecology, 2024)

Prediction of biological nutrients removal in full-scale wastewater treatment plants using H2O automated machine learning and back propagation artificial neural network model: Optimization and comparison - Jingyang Luo; Yuting Luo; Xiaoshi Cheng; Xinyi Liu; Feng Wang; Fang Fang; Jiashun Cao; Weijing Liu; Runze Xu (Bioresource Technology, 2023)

Overexpression of MbICE3 increased the tolerance to cold and drought in lettuce (Lactuca sativa L.) - Yangfan Wei; Zhenghao Li; Long Lv; Qian Yang; Zhi Cheng; Jiaqi Zhang; Wenhao Zhang; Yuting Luan; Aocheng Wu; Wenhui Li; Deguo Han (In Vitro Cellular & Developmental Biology - Plant, 2023)

Deep Bayesian survival analysis of rail useful lifetime - Cheng Zeng; Jinsong Huang; Hongrui Wang; Jiawei Xie; Yuting Zhang (Engineering Structures, 2023)

A simple strategy for obtaining aggregation-induced delayed fluorescence material achieving nearly 20% external quantum efficiency for non-doped solution-processed OLEDs - Yuting He; Cheng Zhang; Hao Yan; Yongshuai Chai; Deyun Zhou (Chemical Engineering Journal, 2023)

Low-carbon economic dispatch of integrated energy systems that incorporate CCPP-P2G and PDR considering dynamic carbon trading price - Yang Cui; Yang Xu; Tao Huang; Yijian Wang; Dingran Cheng; Yuting Zhao (Journal of Cleaner Production, 2023)

Cobalt-modified limonite catalyst for low temperature selective catalytic reduction of NOx in ore sintering flue gas by NH3 - Ting Cheng; Zhaozhong Jiang; Hengjian Zhang; Yuting Hu; Kai Qin; Chengzhu Zhu (Journal of Environmental Chemical Engineering, 2023)

Effects of vegetation restoration on soil aggregates, organic carbon, and nitrogen in the Loess Plateau of China - Bin Wang; Guoce Xu; Tiantian Ma; Li Chen; Yuting Cheng; Peng Li; Zhanbin Li; Yixin Zhang (CATENA, 2023)

Manual correction of genome annotation improved alternative splicing identification of Artemisia annua - Zhaoyu Liu; Yupeng Du; Zhihao Sun; Bohan Cheng; Zenghao Bi; Zhicheng Yao; Yuting Liang; Huiling Zhang; Run Yao; Shen Kang; Yuhua Shi; Huihua Wan; et al. (Planta, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

Research progress on the biosynthesis and delivery of iron–sulfur clusters in the plastid - Bing Yang; Chenyun Xu; Yuting Cheng; Ting Jia; Xueyun Hu (Plant Cell Reports, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Unsustainable water supply from thawing permafrost on the Tibetan Plateau in a changing climate - Taihua Wang; Dawen Yang; Yuting Yang; Guanheng Zheng; Huijun Jin; Xin Li; Tandong Yao; Guodong Cheng (Science Bulletin, 2023)

Surfactant aggravated the antibiotic's stress on antibiotic resistance genes proliferation by altering antibiotic solubilization and microbial traits in sludge anaerobic fermentation - Feng Wang; Le Zhang; Yuting Luo; Yi Li; Xiaoshi Cheng; Jiashun Cao; Junfeng Wu; Haining Huang; Jingyang Luo; Yinglong Su (Science of The Total Environment, 2023)

GSH and H2O2 dynamic correlation in the ferroptosis pathways revealed by engineered probe in tumor and kidney injury - Yuting Wang; Huming Yan; Yongkang Yue; Yongbin Zhang; Fangjun Huo; Fangqin Cheng; Caixia Yin (Chemical Engineering Journal, 2023)

Tumor microenvironment-responsive nanosystem achieves reactive oxygen species self-cycling after photothermal induction to enhance efficacy of antitumor therapy - Yuting Peng; Lianghao Cheng; Chunyi Luo; Fuquan Xiong; Zhiping Wu; Lin Zhang; Peng Zhan; Lishu Shao; Weihua Luo (Chemical Engineering Journal, 2023)

Interpenetrating network expansion sponge based on chitosan and plasma for ultrafast hemostasis of arterial bleeding wounds - Yuting Shi; Wenwen Yu; Xiaoqin Liang; Ju Cheng; Yufei Cao; Mingsheng Liu; Yu Fang; Zheng Yang; Hongbin Liu; Hua Wei; Guanghui Zhao (Carbohydrate Polymers, 2023)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

Exogenous 5-aminolevulinic acid promotes plant growth and salinity tolerance of grape rootstocks in coastal areas - Weiwei Zheng; Yuting Tian; Haili Shi; Miaomiao Chen; Seungbeom Hong; Kai Xu; Jianhui Cheng; Yunxiang Zang (Horticulture, Environment, and Biotechnology, 2023)

Enhancement of seaweed polysaccharides (fucoidan and laminarin) on the phagocytosis of macrophages via activation of intelectin in blunt snout bream (Megalobrama amblycephala) - Hongping Li; Yunlong Liu; Yuting Teng; Yancui Zheng; Minying Zhang; Xu Wang; Hanliang Cheng; Jianhe Xu; Xiangning Chen; Xiaoheng Zhao; Zhujin Ding (Frontiers in Marine Science, 2023)
Fucoidan and laminarin are polymolecular compounds that extracted from seaweed. As functional polysaccharides, they possess various biological functions such as immunomodulatory, anti-inflammatory, antiviral and antioxidant bioactivities. Fucoidan and laminarin modulate host immune responses by activating immune cells (macrophages, neutrophils, T lymphocytes) and inducing the expression of cytokines ( TNFα , IL-1β , IL-6 , IL-8 , NF-κB ). Intelectin is a novel lectin that plays important roles in bacterial agglutination and bactericidal effects by recognizing the polysaccharide components on the cell surface of pathogens, which can also enhance the phagocytosis of macrophages. The present study intends to explore the immunomodulatory effects of fucoidan, laminarin and intelectin on the macrophages of Megalobrama amblycephala . The results showed that the incubation of both fucoidan and laminarin at the concentration of 100 μg/mL for 4 h could enhance the phagocytic capacity of M. amblycephala macrophages, which also showed remodeled cytoskeleton with extended pseudopodia. In addition, fucoidan and laminarin could induce the expression of M. amblycephala intelectin (MaINTL) in the primary hepatocytes and macrophages, and the recombinant MaINTL (rMaINTL) could bind with fucoidan and laminarin. Furthermore, fucoidan and laminarin induced the expression of cytoskeletal remodeling related genes in the primary M. amblycephala macrophages, such as Rac1 and WASP , which should contribute to the enhancement of seaweed polysaccharides (fucoidan and laminarin) and MaINTL on the phagocytosis of M. amblycephala macrophages. However, even though fucoidan and laminarin could induced the expression of CXCL8 , while the chemotaxis of M. amblycephala macrophages on neutrophils was not affected by them. These findings suggested that fucoidan and laminarin enhanced the phagocytic capacity of M. amblycephala macrophages via activation of MaINTL and up-regulation of the expression of downstream cytoskeletal remodeling related genes Rac1 and WASP . Therefore, fucoidan and laminarin could be used as immune enhancers to improve host immunity and disease resistance in M. amblycephala , which provided novel insights into the prevention and protection of fish bacterial diseases.

One-pot synthesis of novel flower-like LaCO3OH adsorbents for efficient scavenging of phosphate from wastewater - Fulong Cheng; Fangui Nie; Yuting Fan; Dan Huang; Yinian Wang; Jianxin Fan (Environmental Science and Pollution Research, 2023)

Effects of driving factors at multi-spatial scales on seasonal runoff and sediment changes - Guoce Xu; Yuting Cheng; Chaozhi Zhao; Jinsha Mao; Zhanbin Li; Lu Jia; Yixin Zhang; Bin Wang (CATENA, 2023)

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Deficiency of NLR family member NLRC5 alleviates alcohol induced hepatic injury and steatosis by enhancing autophagy of hepatocytes - Yuting Wu; Cheng Huang; Tianlu Shi; Jun Li (Toxicology and Applied Pharmacology, 2023)

Positivity and difference of influence of built environment around urban park on building energy consumption - Peng Wang; Yuting Yang; Cheng Ji; Lei Huang (Sustainable Cities and Society, 2023)

Influence of built environment on building energy consumption: a case study in Nanjing, China - Peng Wang; Yuting Yang; Cheng Ji; Lei Huang (Environment, Development and Sustainability, 2023)

Corrigendum to: Impacts of farmland application of antibiotic-contaminated manures on the occurrence of antibiotic residues and antibiotic resistance genes in soil: A meta-analysis study [Chemosphere 300 (Aug 2022) 134529] - Yu Zhang; Dengmiao Cheng; Jun Xie; Yuting Zhang; Yu Wan; Yueqiang Zhang; Xiaojun Shi (Chemosphere, 2023)

Identification of a novel α-glucosidase inhibitor from Melastoma dodecandrum Lour. fruits and its effect on regulating postprandial blood glucose - Yang Xu; Ahmed K. Rashwan; Zhiwei Ge; Yuting Li; Hengju Ge; Jiaxin Li; Jiahong Xie; Shiyu Liu; Jie Fang; Kejun Cheng; Wei Chen (Food Chemistry, 2023)

Emerging electrocatalytic activities in transition metal selenides: synthesis, electronic modulation, and structure-performance correlations - Yuting Deng; Sutong Xiao; Yijuan Zheng; Xiao Rong; Mingru Bai; Yuanjiao Tang; Tian Ma; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2023)

Characteristics of Zn Content and Localization, Cu–Zn SOD, and MT Levels in the Tissues of Marginally Zn-Deficient Mice - Ziqiong Wang; Cheng Peng; Yuting Zhang; Lei Wang; Lu Yu; Chunhong Wang (Biological Trace Element Research, 2023)

Monte Carlo seismic response analysis of permafrost sites: a case study - Xiaobo Yu; Rui Zhang; Yushun Cheng; Yuting Hu (Natural Hazards, 2022)

Mechanisms of Interannual Variability of Ocean Bottom Pressure in the Southern Indian Ocean - Yuting Niu; Xuhua Cheng; Jianhuang Qin; Niansen Ou; Chengcheng Yang; Duotian Huang (Frontiers in Marine Science, 2022)
The study of ocean bottom pressure (OBP) helps to understand the changes in the sea level budget and ocean deep circulation. In this study, the characteristics and mechanisms of interannual OBP variability in the Southern Indian Ocean are examined using Gravity Recovery and Climate Experiment (GRACE) satellite data from 2003 to 2016. Results show that there are two energetic OBP centers in the Southern Indian Ocean (50°–60°S, 40°–60°E and 45°–60°S, 80°–120°E). The OBP magnitudes at two centers have strong variability on interannual time scales, and their values are larger during austral summer (NDJF) and winter (JJAS). Atmospheric forcing plays an important role in local OBP variability. The high (low) sea level pressure (SLP) over the Southern Indian Ocean benefits positive (negative) OBP anomalies via the convergence (divergence) of Ekman transport driven by local wind. Such SLP anomalies are related to the Southern Annular Mode (SAM), Southern Oscillation (SO) and Indian Ocean dipole (IOD). SAM can influence the OBP changes in both austral summer and winter, while SO and IOD have positive correlations with OBP variability during austral summer and austral winter, respectively. These results are validated by a mass-conservation ocean model, which further confirms the importance of atmospheric forcing on the interannual OBP variations.

Response of water quality to land use in hydrologic response unit and riparian buffer along the Dan River, China - Xiaojun Liu; Yi Zhang; Zhanbin Li; Peng Li; Guoce Xu; Yuting Cheng; Tiegang Zhang (Environmental Science and Pollution Research, 2021)

Research on the influence of land use change to habitat of cranes in Shengjin Lake wetland - Lei Fang; Bin Dong; Cheng Wang; Fei Yang; Yanglin Cui; Wenrui Xu; Liang Peng; Yuting Wang; Haoran Li (Environmental Science and Pollution Research, 2020)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

Spatial and temporal stability of temperature in the first-level basins of China during 1951–2013 - Yuting Cheng; Peng Li; Guoce Xu; Zhanbin Li; Shengdong Cheng; Bin Wang; Binhua Zhao (Theoretical and Applied Climatology, 2019)

An oilseed rape WRKY-type transcription factor regulates ROS accumulation and leaf senescence in Nicotiana benthamiana and Arabidopsis through modulating transcription of RbohD and RbohF - Liu Yang; Chaofei Ye; Yuting Zhao; Xiaolin Cheng; Yiqiao Wang; Yuan-Qing Jiang; Bo Yang (Planta, 2018)

Acute Toxicity of Imidazole Nitrate Ionic Liquids with Varying Chain Lengths to Earthworms (Eisenia foetida) - Yuting Shao; Zhongkun Du; Cheng Zhang; Lusheng Zhu; Jinhua Wang; Jun Wang (Bulletin of Environmental Contamination and Toxicology, 2017)

Biodegradation of Endosulfan by Bacterial Strain Alcaligenes faecalis JBW4 in Argi-Udic Ferrosols and Hapli-Udic Isohumosols - Yu Zhang; Lusheng Zhu; Jinhua Wang; Jun Wang; Benying Su; Cheng Zhang; Yuting Shao; Chao Li (Water, Air, & Soil Pollution, 2016)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)